Harnessing historical genebank data to accelerate pea breeding - Lanique Niels; Jochen Christoph Reif; Lars-Gernot Otto; Vilson Mirdita; Markus Oppermann; Ulrike Lohwasser; Matthias Kotter; Stephan Weise; Samira El Hanafi (Theoretical and Applied Genetics, 2025)
The German Federal Ex Situ Genebank for Agricultural and Horticultural Crops (IPK) harbours over 3000 pea plant genetic resources (PGRs), backed up by corresponding information across 16 key agronomic and economical traits. The unbalanced structure and inconsistent format of this historical data has precluded effective leverage of genebank accessions, despite the opportunities contained in its genetic diversity. Therefore, a three-step statistical approach founded in linear mixed models was implemented to enable a rigorous and targeted data curation. Spring accessions revealed considerable breeding potential, with protein content exceeding market standards by almost one-fifth and with hundred grain weight that could match the upper limits reported for European elite varieties. This variation is embedded within structured populations, comprising five convarieties including sugar snaps and field pea, adding value for breeding across diverse morphotypes and market segments. Winter accessions demonstrated cold resilience, with post-winter survival rate up to 79.27% under minimum temperatures as low as − 17.1 °C. This variation is of particular relevance given the limited availability of winter-hardy cultivars able to evade summer drought and heat stresses. Transformation of the IPK Genebank into a bio-digital resource redirects formerly static material into central leverage for plant breeding in view of contemporary challenges. As such, this investigation activated the IPK pea population for use in among others breeding for a wide variety of ideotypes, research into adaptation, and future combination with omics studies.

Heterozygous loss-of-function variants in DOCK4 cause neurodevelopmental delay and microcephaly - Charlotte Herbst; Viktoria Bothe; Meret Wegler; Susanne Axer-Schaefer; Séverine Audebert-Bellanger; Jozef Gecz; Benjamin Cogne; Hagit Baris Feldman; Anselm H. C. Horn; Anna C. E. Hurst; Melissa A. Kelly; Michael C. Kruer; et al. (Human Genetics, 2024)
Neurons form the basic anatomical and functional structure of the nervous system, and defects in neuronal differentiation or formation of neurites are associated with various psychiatric and neurodevelopmental disorders. Dynamic changes in the cytoskeleton are essential for this process, which is, inter alia, controlled by the dedicator of cytokinesis 4 ( DOCK4 ) through the activation of RAC1 . Here, we clinically describe 7 individuals (6 males and one female) with variants in DOCK4 and overlapping phenotype of mild to severe global developmental delay. Additional symptoms include coordination or gait abnormalities, microcephaly, nonspecific brain malformations, hypotonia and seizures. Four individuals carry missense variants (three of them detected de novo) and three individuals carry null variants (two of them maternally inherited). Molecular modeling of the heterozygous missense variants suggests that the majority of them affect the globular structure of DOCK4. In vitro functional expression studies in transfected Neuro-2A cells showed that all missense variants impaired neurite outgrowth. Furthermore, Dock4 knockout Neuro-2A cells also exhibited defects in promoting neurite outgrowth. Our results, including clinical, molecular and functional data, suggest that loss-of-function variants in DOCK4 probable cause a variable spectrum of a novel neurodevelopmental disorder with microcephaly.

Choosing the right tool: Leveraging of plant genetic resources in wheat (Triticum aestivum L.) benefits from selection of a suitable genomic prediction model - Marcel O. Berkner; Albert W. Schulthess; Yusheng Zhao; Yong Jiang; Markus Oppermann; Jochen C. Reif (Theoretical and Applied Genetics, 2022)
Key message Genomic prediction of genebank accessions benefits from the consideration of additive-by-additive epistasis and subpopulation-specific marker effects. Abstract Wheat ( Triticum aestivum L.) and other species of the Triticum genus are well represented in genebank collections worldwide. The substantial genetic diversity harbored by more than 850,000 accessions can be explored for their potential use in modern plant breeding. Characterization of these large number of accessions is constrained by the required resources, and this fact limits their use so far. This limitation might be overcome by engaging genomic prediction. The present study compared ten different genomic prediction approaches to the prediction of four traits, namely flowering time, plant height, thousand grain weight, and yellow rust resistance, in a diverse set of 7745 accession samples from Germany’s Federal ex situ genebank at the Leibniz Institute of Plant Genetics and Crop Plant Research in Gatersleben. Approaches were evaluated based on prediction ability and robustness to the confounding influence of strong population structure. The authors propose the wide application of extended genomic best linear unbiased prediction due to the observed benefit of incorporating additive-by-additive epistasis. General and subpopulation-specific additive ridge regression best linear unbiased prediction, which accounts for subpopulation-specific marker-effects, was shown to be a good option if contrasting clusters are encountered in the analyzed collection. The presented findings reaffirm that the trait’s genetic architecture as well as the composition and relatedness of the training set and test set are major driving factors for the accuracy of genomic prediction.

Unlocking historical phenotypic data from an ex situ collection to enhance the informed utilization of genetic resources of barley (Hordeum sp.) - Maria Y. González; Norman Philipp; Albert W. Schulthess; Stephan Weise; Yusheng Zhao; Andreas Börner; Markus Oppermann; Andreas Graner; Jochen C. Reif (Theoretical and Applied Genetics, 2018)

Towards a generic procedure for the detection of relevant contaminants from waste electric and electronic equipment (WEEE) in plastic food-contact materials: a review and selection of key parameters - Franky Puype; Jiří Samsonek; Věra Vilímková; Šárka Kopečková; Andrea Ratiborská; Jan Knoop; Marion Egelkraut-Holtus; Markus Ortlieb; Uwe Oppermann (Food Additives & Contaminants: Part A, 2017)

The Garlic and Shallot Core Collection image database of IPK presenting two vegetatively maintained crops in the Federal ex situ genebank for agricultural and horticultural crops at Gatersleben, Germany - Christian Colmsee; E. R. Joachim Keller; Christine Zanke; Angelika Senula; Thomas Funke; Markus Oppermann; Stephan Weise; Uwe Scholz (Genetic Resources and Crop Evolution, 2012)